Just say please - " Mayer , Mercer " (NEW YORK Golden books, 1998)
"Just Say Please" is a children's book by Mercer Mayer, featuring his beloved character, Little Critter. In this story, Little Critter learns about good manners at school and strives to apply them at home. The narrative emphasizes the importance of saying "please" and "thank you," highlighting how these simple phrases can positively impact interactions with others. The book is part of the Little Golden Book series, known for its engaging stories and illustrations that teach valuable life lessons to young readers.